Exploring transnational entrepreneurship. Immigrant entrepreneurs and foreign-born returnees in the Italian ICT sector. (3rd September 2019) - Brzozowski, Jan; Cucculelli, Marco; Surdej, Aleksander
Abstract : This explorative paper contributes to the expanding literature on immigrant transnationalism by investigating the determinants of transnational entrepreneurial behavior among two groups of foreign-born entrepreneurs from emerging and developing countries who settled in Italy: foreign-born returnees (i.e., foreign-born individuals of Italian origin) and immigrants (i.e., persons without Italian ethnic origin). Using a large data-set on immigrant entrepreneurs in the Italian ICT sector, we have found foreign-born returnees to be less likely to engage in transnational entrepreneurship activity than immigrant entrepreneurs of non-Italian descent. Foreign-born returnees are mostly linked with economic activities focused on the domestic (Italian) market, while other immigrants much often turn their entrepreneurial activities back to home countries, but also their firms tend to be more internationalized. Therefore, we argue that the multicultural experience of foreign-born returnees constitutes an unexploited potential for the ICT sector in Italy, especially within the context of the internationalization prone ICT entrepreneurship.